Custo do absenteísmo e cancelamento de serviços em um ambulatório médico de especialidade - Canela, Cláudia Cristina Costa (2018)
The Specialty Care Clinic is a health organization that acts as a center for diagnosis and management guidance. Today, one of the challenges of managers of these health institutions is to intercept absenteeism or appointment cancellations, and the search for the effective use of the resources of the Brazilian Unified Health System (SUS). Objective: To investigate occurrences, basis and costs generated by the absenteeism and cancellations at the Specialty Care Clinics. Method: Exploratory study, analytical descriptive, quantitative with longitudinal cut (2015 and 2016) with the methodology applied at the Brazilian Medical Specialty Care Clinic (AME) that takes care of 30 municipalities at the northwestern part of São Paulo. Several internal secondary data sources were obtained by the Clinic’s information system, cost management and administrative audit reports. In addition, the data was statistically analysed by the Rx64 software, version 2.13.0, and The R Foundation for Statistical Computing. Results: The average rate of absenteeism was 17.12% in (2015) and 16.13% in (2016), reflecting a cost of R$ 1.558.579.52 in (2015) and R$ 1.342,956.00 in (2016), with a reduction of R$ 215.623,52 (13.8%). Among the 30 different specialties offered by the AME, those that had the highest cost in relation to the absences was: Orthopedics, R$ 116.670,06 - 7.89% in (2015), and Dermatology, R$ 99.167,76 - 6.95% in (2016). Among the five non-medical specialties, physiotherapy was the one with the highest cost with absences in 2015 (14.51%) - R$ 133.321,23 and in 2016 (19.30%) - R$ 159.392,10. In regarding the appointments and examination cancellations, the cancellation fee was 0.5%, with 883 medical and non medical cancellations with a cost of R$ 55.128,7 (US $ 15,578.71) and 1.20% with 1.304 exams cancellations with a cost of R$ 212.633,61 (US $ 62,467.03). Conclusion: Knowing the appointment users absenteeism and the cancellation of appointments/exams indicators, provides subsidies for management, since, in addition to guiding the waiting queue management, the processes decision making, it also awakens to the importance of awareness of the co-responsibility of the user of the effective use of public health resources.